A 1‐D model of physical chemistry in Saturn's inner magnetosphere. Issue 8 (5th August 2013) - Fleshman, B. L.; Delamere, P. A.; Bagenal, F.; Cassidy, T.
Abstract : [1] Water vapor spewed out of Enceladus' geysers spreads across the Saturn system through dissociation, charge exchange, and neutral‐neutral collisions. The combined effects of impact ionization by suprathermal electrons, charge‐exchange between ions and neutrals, and radial transport of the plasma produce the observed distribution of ions and their temperature in the magnetosphere of Saturn. In this paper we combine our physical chemistry model with the neutral cloud model of Cassidy and Johnson (2010) to explore how the spatial distributions of hot electrons and of neutrals, as well as radial transport rates, produce the observed ion properties between 4 and 10 R S (where R S is the radius of Saturn). We investigate the sensitivity of the model output to radial transport rates and the radial profile of hot electron density. Selected results are as follows: (1) Hot electrons (e.g., tens to hundreds eV) at 4 R S (Enceladus' orbit) make up between ≈0.25% and 0.5% of the total electron density, consistent with our previous findings, increasing to ∼10% at 10 R S . (2) The region over which chemistry plays a dominant role extends to 7 R S . Beyond 7 R S radial transport takes over, establishing the rate of plasma outflow from Saturn's plasma torus. (3) The plasma radial transport rate at 10 R S is found to be between 20 and 80 kg/s for reasonable choices of hot electron density, radial transport rate, and neutral hydrogen and H2 O densities. Key Points: Model the plasma sheet properties of Saturn's inner magnetosphere Investigate sensitivity to hot electrons, neutral density, and radial transport Determine the radial plasma mass outflow rate